Aboriginal Site Specific Maths Project (ASSMP) : Problem Solving in a Culturally Defined Context. - Hurley, Robyn ([Batchelor College], 1998)
This is a final report of an Aboriginal site specific maths project funded by the Committee for University Teaching and Staff development. The report details the project's aims, outcomes, rationale and methodology, and provides information about the literature review and project assessment. During the project teacher education students from Batchelor College: employed problem solving strategies to teach mathematics in their respective leaning environments; developed community based teaching/learning materials to teach problem solving skills and mathematics; developed strategies which enable the teaching of mathematical concepts in both cultures; understood the processes involved in developing community based curriculum; taught mathematics in own language and English; developed a transferable of problem solving activities which model the process of developing community based curriculum material.